Teaching and Researching the History and Archaeology of Jordan during the Bronze and Iron Ages (ca. 3600 – 1200 BC) - Kafafi, Zeidan A. (Jordan Journal for History and Archaeology, 2023)
The history of nations is their political and cultural identity, but this recorded history, which began with the knowledge of writing in the East about 3200 years BC and has continued until the present, has seen difficulties and declines in civilizations. What concerns us in this article is shedding light on an important period of Jordan’s ancient history – the Bronze and Iron Ages (c. 3600-332 BC) – which scholars of religion and the Bible contect with stories in the Bible beginning with the the Israelites leaving Egypt, their coming to Palestine and their establishing their state. It is important for us to shed light on who undertook and undertakes recording that history and the methodologies followed and the interpretation of antiquities and ancient inscriptions related to that history. We have seen that it is necessary to the extent possible to clarify Jordan’s role in the study of Jordan’s ancient history by the Jordanian universities that study history and archaeology and related fields. Since the establishment of the emirate in 1921, Jordan has attached great importance to archaeology, establishing a Department of Antiquities that remained under the control of the Mandate until the Arabization of the army in 1956. Also, in the same year in which the University of Jordan was established (1962), a Department of History and Archeology was established, and the university sent students abroad to study ancient history. Some other Jordanian universities did likewise. Unfortunately, recent years have seen a decline in research and teaching about the Bronze and Iron Ages; a number of faculty members in this field have retired, and universities have either refrained from sending students abroad or have stopped hiring new faculty members. In addition, the sub-sciences related to archaeology have overshadowed the original, hoping that students will get a job, as a result of graduates in archaeology flooding the market. In order for the matter to be rectified, it is necessary to establish a research center or centers based on scientific research and publishing in the ancient history of Jordan, following a unified approach based on scientific evidence.